Population structure and genetic diversity of false killer whales (Pseudorca crassidens) in New Zealand waters: preliminary results - Tezanos-Pinto G; Bohorquez L; Zaeschmar JR; Stockin K; Carroll EL; Caballero-Gaitan S (Taylor and Francis Group, 2024)
False killer whales (Pseudorca crassidens) are globally distributed cetaceans, often found in deep oceanic waters but occasionally near coastlines. Despite their broad distribution, information on their abundance, genetics, and ecology remains limited. In New Zealand waters, these whales occur year-round, with increased sightings during the warmer months due to the East Auckland Current. This study investigates the genetic diversity and population structure of New Zealand false killer whales using 17 samples collected from 2005 to 2018 in four locations, comparing them to global studies. New Zealand samples revealed four unique haplotypes with low genetic diversity (h = 0.42 ± 0.141; π = 0.29%± 0.002). No genetic differentiation was observed between South Pacific and New Zealand populations (FST= 0.05 p = 0.1602 (Formula presented.) ST= 0.058 p = 0.145). These findings suggest low genetic diversity for New Zealand false killer whales, but within values expected for other cetaceans with matrilineal social structures. The presence of shared haplotypes suggests potential historical or ongoing connections with wider Pacific populations. However, further research is needed due to the short mtDNA-CR fragment analysed and small sample size, which may have resulted in an inability to capture the full extent of the genetic variation. This study contributes to our understanding of this species and its conservation within New Zealand.
Keywords: False killer whales; genetic diversity; mt-DNA; population structure; New Zealand; marine mammal; delphinidae